2006
DOI: 10.2169/internalmedicine.45.1217
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Infection of Mycobacterium aviumintracellulare Complex with Simultaneous Organizing Pneumonia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Recently, cases with certain clinical features have been reported: NTM disease accompanied by histologically-proven organizing pneumonia (OP), also known as bronchiolitis obliterans organizing pneumonia (2,3), in which patients developed acute or subacute symptoms with infiltrates on chest images, and improved dramatically following treatment with a combination of a corticosteroid and antimycobacterial therapy (4)(5)(6). We also found similar cases among our NTM disease patients.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Recently, cases with certain clinical features have been reported: NTM disease accompanied by histologically-proven organizing pneumonia (OP), also known as bronchiolitis obliterans organizing pneumonia (2,3), in which patients developed acute or subacute symptoms with infiltrates on chest images, and improved dramatically following treatment with a combination of a corticosteroid and antimycobacterial therapy (4)(5)(6). We also found similar cases among our NTM disease patients.…”
Section: Introductionsupporting
confidence: 77%
“…Similar cases have been reported in the literature. For example, Hamada et al (4) reported the case of a 67-year-old woman with fever and dyspnea. Her sputa culture confirmed Mycobacterium intracellulare, and TBLB revealed OP that rapidly improved clinically with corticosteroid administration.…”
Section: Discussionmentioning
confidence: 99%
“…5 Mycobacterium avium intracellulare complex is rarely associated with BOOP, and we found no mention in the literature of Mycobacterium kansasii as an etiology of BOOP. [6][7][8] To our knowledge, this is the first report of BOOP associated with Mycobacterium kansasii infection.…”
Section: Introductionmentioning
confidence: 74%
“…7 Coincident appearances of granulomata and organizing pneumonia in a transbronchial biopsy specimen had not been previously described in mycobacterial disease.…”
Section: Discussionmentioning
confidence: 94%
“…Pulmonary NTM disease is the most common type of involvement and occurs primarily in patients with preexisting structural lung damage such as emphysema or On the other hand, rare cases with different disease entities have been reported: NTM disease accompanied by histologically proven OP in which patients developed acute or subacute symptoms with infiltrates on chest images, and improved rapidly following treatment with a combination of a corticosteroid and anti-mycobacterial therapy (6,(8)(9)(10). Hamada et al (8) reported a 67-year-old woman with fever and dyspnea; her sputum culture confirmed Mycobacterium intracellulare, and transbronchial lung biopsy (TBLB) revealed OP that showed dramatic clinical improvement clinically with corticosteroid and anti-mycobacterial treatment (clarithromycin, rifampicin, and levofloxacin).…”
Section: Discussionmentioning
confidence: 99%